2020
DOI: 10.5761/atcs.oa.19-00040
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Carina and Lobar Bronchi Stenting in Patients with Advanced Lung Cancer: Is It Worth the Effort? A Clinical Experience

Abstract: Background: The lobar airway stenting remains an endoscopic procedure not well standardized in patients with locally advanced lung cancer disease. The goal of this study was to evaluate technical feasibility, clinical outcome, and complications of different stents in patients with malignant lesions involving lobar bronchi, primary and secondary carina. Methods: Between November 2008 and October 2013, we retrospectively analyzed 146 patients with benign and malignant tracheobronchial stenosis who underwent airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…DiBardino et al, however published a study where lung transplant patients did not find benefit, but this was a small group of five patients [13]. A retrospective study by Marchese et al reported outcomes of 51 patients with malignant stenosis at secondary carinae and lobar airways [6]. Improvement was noted in mMRC (2.6 AE 0.8 vs. 1.2 AE 0.5; P < 0.01) with a small number of complications; migration in 11% was most common.…”
Section: Indications and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…DiBardino et al, however published a study where lung transplant patients did not find benefit, but this was a small group of five patients [13]. A retrospective study by Marchese et al reported outcomes of 51 patients with malignant stenosis at secondary carinae and lobar airways [6]. Improvement was noted in mMRC (2.6 AE 0.8 vs. 1.2 AE 0.5; P < 0.01) with a small number of complications; migration in 11% was most common.…”
Section: Indications and Patient Selectionmentioning
confidence: 99%
“…Predictors of clinical success, specifically among malignant airway obstruction (MAO) have been reported [4]. Stenting is typically considered only for trachea and main bronchi, but evolving literature has described the benefit of lobar stenting in selected patients [5][6][7][8]. Nonmalignant obstruction tends to be more complex ranging from endobronchial inflammation, scars to loss of cartilaginous airway support or malacia.…”
Section: Indications and Patient Selectionmentioning
confidence: 99%
“…Marchese et al (2020) conducted a retrospective chart review involving 51 patients with advanced unresectable lung cancer. The mean age was 67, with 41 males and 10 females [ 16 ]. Marchioni et al (2020) conducted a multicentric retrospective study with 100 patients with central airway obstruction, focusing on integrated treatment (60 patients) versus standard treatment (40 patients).…”
Section: Reviewmentioning
confidence: 99%
“…The location of the lesion and obstruction was categorized based on different areas, including the trachea, main right bronchus, main left bronchus, carina, and extensive involvement. The degree of obstruction (IQR) for each category was reported, while no additional information was provided regarding dyspnea grade, stenosis type, or blood gas parameters [ 16 ]. Miyazawa et al reported pulmonary function testing results in their study, including vital capacity (VC), forced vital capacity (FVC), peak expiratory flow (PEF), and various stenosis types.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation